Empagliflozin Alleviates Carfilzomib-Induced Cardiotoxicity in Mice by Modulating Oxidative Stress, Inflammatory Response, Endoplasmic Reticulum Stress, and Autophagy - Mina Y. George; Mohamed S. Dabour; Eman Rashad; Beshay N. Zordoky (MDPI AG, 2024)
Carfilzomib is an irreversible proteasome inhibitor used for multiple myeloma patients. However, carfilzomib treatment is associated with cardiovascular complications. Empagliflozin, an Sodium Glucose Co-transporter 2 inhibitor (SGLT-2) inhibitor, is an oral antidiabetic drug with proven antioxidant and anti-inflammatory properties. The aim of the present study was to determine the cardioprotective effects of empagliflozin against carfilzomib-induced cardiotoxicity. C57BL/6 mice were randomly divided into four groups: control, empagliflozin, carfilzomib, and carfilzomib + empagliflozin. Empagliflozin prevented carfilzomib-induced cardiotoxicity by ameliorating histological alterations, CK-MB, and troponin-I. Moreover, it inhibited carfilzomib-induced oxidative damage and inflammation via its action on catalase activity, reduced glutathione levels and superoxide dismutase activity, and reduced nuclear factor-κB (p65) and cytokine levels. Mechanistically, empagliflozin abrogated endoplasmic reticulum stress induced by carfilzomib, as evidenced by the effect on the Glucose Regulated Protein-78 (GRP-78)/Activating Transcription Factor 6 (ATF6)/C/EBP homologous protein (CHOP) axis. Intriguingly, carfilzomib significantly induced autophagy, an effect that was further enhanced by empagliflozin, evidenced by increased LC3B and beclin-1 mRNA expression and reduced p62 expression. The effect of empagliflozin on apoptosis was confirmed by reduced expression of active caspase-3. Importantly, empagliflozin did not alter the cytotoxic effect of carfilzomib on human U266B1 multiple myeloma cells. our findings suggest that empagliflozin may provide a new therapeutic strategy to mitigate carfilzomib-induced cardiotoxicity in multiple myeloma patients.